Ca2+-Independent Exocytosis Favors Axonal Release through Enlarged Fusion Pores in Sensory Neurons - Rong Huang; Xingyu Du; Qihui Wu; Yuan Wang; Yuqi Hang; Xi Wu; Yiman Li; Jie Li; Zhongjun Qiao; Yinglin Li; Lili Yin; Xiaoxuan Sun; et al. (Neuroscience Bulletin, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Astrocyte-Derived CXCL10 Induces Neuronal Tau Hyperphosphorylation and Cognitive Impairments in Sepsis - Cuiping Guo; Hang Ruan; Wensheng Li; Yi Liu; Abdoul Razak Yacoubou Mahaman; Qian Guo; You Zhou; Rong Liu; Jianzhi Wang; Chenliang Zhou; Xiaochuan Wang; Shusheng Li (Neuroscience Bulletin, 2026)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Ventral Hippocampal CA1 GADD45B Regulates Susceptibility to Social Stress by Influencing NMDA Receptor-Mediated Synaptic Plasticity - Mengbing Huang; Jian Bao; Xiaoqing Tao; Yifan Niu; Kaiwei Li; Ji Wang; Xiaokang Gong; Rong Yang; Yuran Gui; Hongyan Zhou; Yiyuan Xia; Youhua Yang; et al. (Neuroscience Bulletin, 2025)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Ventromedial Thalamus-Projecting DCN Neurons Modulate Associative Sensorimotor Responses in Mice - Jie Zhang; Hao Chen; Li-Bin Zhang; Rong-Rong Li; Bin Wang; Qian-Hui Zhang; Liu-Xia Tong; Wei-Wei Zhang; Zhong-Xiang Yao; Bo Hu (Neuroscience Bulletin, 2022)

Digoxin Ameliorates Glymphatic Transport and Cognitive Impairment in a Mouse Model of Chronic Cerebral Hypoperfusion - Jie Cao; Di Yao; Rong Li; Xuequn Guo; Jiahuan Hao; Minjie Xie; Jia Li; Dengji Pan; Xiang Luo; Zhiyuan Yu; Minghuan Wang; Wei Wang (Neuroscience Bulletin, 2022)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Effect of Apolipoprotein E Genotypes on Huntington’s Disease Phenotypes in a Han Chinese Population - Xiao-Yan Li; Yan-Bin Zhang; Miao Xu; Hong-Rong Cheng; Yi Dong; Wang Ni; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2019)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

Atlas of the Striatum and Globus Pallidus in the Tree Shrew: Comparison with Rat and Mouse - Rong-Jun Ni; Zhao-Huan Huang; Yu-Mian Shu; Yu Wang; Tao Li; Jiang-Ning Zhou (Neuroscience Bulletin, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Cerebral vasculopathy in a Chinese family with neurofibromatosis type I mutation - Jian-Tao Liang; Li-Rong Huo; Yu-Hai Bao; Zhen-Yu Wang; Feng Ling (Neuroscience Bulletin, 2013)

Possible novel roles of poly(rC)-binding protein 1 in SH-SY5Y neurocytes: an analysis using a dynamic Bayesian network - Li-Rong Huo; Jian-Tao Liang; Jun-Hua Zou; Lan-Ying Wang; Qi Li; Xiao-Min Wang (Neuroscience Bulletin, 2012)

Morphological changes of cholinergic nerve fibers in the urinary bladder after establishment of artificial somatic-autonomic reflex arc in rats - Han-Zhi Wang; Shu-Rong Li; Can Wen; Chuan-Guo Xiao; Bing-Yin Su (Neuroscience Bulletin, 2007)

Intergeneration CAG expansion in a Wuhan juvenile-onset Huntington disease family - Yuan Liu; Yan Shen; He Li; Hui Wang; Zhen-Rong Yang; Yan Chen; Yan-Ping Tang (Neuroscience Bulletin, 2007)